Edukasi Pemanfaatan Limbah Lokal dalam Produksi Enzim: Strategi Meningkatkan Minat Belajar Biokimia - Yunita Arian Sani Anwar; Muti’ah Muti’ah; Indra Cipta; Dini Hardianti; Diah Kartika Sari (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Bantiran Village, located in Pupuan District, Tabanan Regency, possesses significant agricultural and plantation potential, particularly in horticultural commodities such as durian, mangosteen, and cocoa. However, the high level of production also generates a considerable quantity of substandard fruits that do not meet market visual standards. This condition contributes to increased food loss at both the farmer and community levels. This Economy Social Activity (ESA) program aimed to utilize substandard fruits through product innovation by processing them into ice cream based on local resources. The methods employed included field observation, socialization, ice cream-making training, and evaluation. The activity was conducted on April 25, 2026, involving the local community of Bantiran Village, particularly members of the Family Welfare Empowerment (PKK) group and farmer groups. The results demonstrated an improvement in community understanding of the concept of substandard fruits, their processing potential, and practical skills in producing ice cream made from substandard cocoa fruits. The resulting product exhibited favorable taste, aroma, and texture characteristics and showed potential for commercialization as an additional source of income. This activity indicates that local resource-based product innovation can serve as an effective strategy to reduce food loss while enhancing the economic value of rural communities.